1972
DOI: 10.1021/ma60028a030
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Solvent on Polymer Incompatibility in Solution

Abstract: It is generally held that the incompatibility of polymers in solution arises from an unfavorable interaction (X23) between segments of the polymers and is independent of the polymer-solvent interactions (Xi2 and Xi3). This is correct when the polymer-solvent interactions are of equal magnitude, as assumed in Scott's original treatment of such ternary systems. We reexamine the theory, calculating spinodals which show that a small difference in polymer-solvent interactions has a marked effect on polymer incompat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
104
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 185 publications
(109 citation statements)
references
References 0 publications
4
104
0
1
Order By: Relevance
“…These results were consistent with the previously published studies. 1,2,4,7,21,22 To further determine their multipotential differentiation capability, trilineage differentiation toward adipocytes, osteoblast, and chondrocytes was induced with specific induction medium. hADSCs show their stem cell properties and can also be specifically induced into NLCs by a cocktail induction protocol, which is consistent with the previous reports.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…These results were consistent with the previously published studies. 1,2,4,7,21,22 To further determine their multipotential differentiation capability, trilineage differentiation toward adipocytes, osteoblast, and chondrocytes was induced with specific induction medium. hADSCs show their stem cell properties and can also be specifically induced into NLCs by a cocktail induction protocol, which is consistent with the previous reports.…”
Section: Figmentioning
confidence: 99%
“…20,21 Chitosan, a naturally abundant degradable polysaccharide, has been used to prepare porous scaffolds for stem cell-based tissue regeneration. For example, Schwartz et al reported that chitosan is quite suitable for the induction of the chondrogenic differentiation of the human bone marrow mesenchymal stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…Let us consider the effect of ionic strength on the phase state from the point of view of the general theoretical concepts relative to the relations between the intensity of polymer-solvent and polymerpolymer interactions, and the phase state of polymer/polymer/solvent systems. 2,50,51 Compatibility between caseinate and guar in water at low ionic strength when the pH is above the isoelectric point of casein can be ascribed to two causes: the formation of weak soluble interpolymer complexes, which dissociate when ionic strength rises; and/or the vanishing of the difference in the thermodynamic interaction parameter between each of the biopolymers and water. The second one seems unlikely, because caseinate is thermodynamically incompatible with PEG in the absence, as well as in the presence, of salt (Fig.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 98%
“…Zeman and Patterson [1] were the first to demonstrate in their study of polymer solutions that the phase behavior in ternary systems was determined mainly by the asymmetry in the polymer-solvent interactions, the so-called ⌬ effect (⌬ = 12 Ϫ 13 ), which has been illustrated for a number of systems [2][3][4][5][6]. However, until now, little work on the influence of the difference of molecular weights between different components on the asymmetry of the polymer-polymer interactions has been reported [7].…”
Section: Introductionmentioning
confidence: 98%
“…In a binary polymer blend (designated components 1 and 2), there is only one binary interaction pair (1)(2), and miscibility in the system is judged by the criterion 12 р 12 crit , where crit = 0.5 (N Ϫ 0. and N i is the degree of polymerization of component i. There are three such binary pairs (1-2, 1-3 and 2-3) in a ternary polymer blend (designated 1, 2 and 3), and the interaction between any two of the components will be influenced by the third one, which has the opportunity to interact with other components as well.…”
Section: Introductionmentioning
confidence: 99%